THE EFFECT OF PROBLEM BASED LEARNING MODEL ON STUDENTS LEARNING RESULTS AND STUDENTS' PROBLEM SOLVING SKILLS - Johannes Febriko Napitupulu; Mariati Purnama Simanjuntak; Johan Sinurat (ISER (Indonesian Science Education Research), 2019)
This study focused on the influence of problem-based learning (PBL) models on student learning outcomes and students' problem-solving skills, the improvement of student learning outcomes and KPM, and the improvement of each indicator. This research was quasi-experiment. The population of this study were all class X Senior High School 4 Medan totalling ten classes. Sampling was done by simple random sampling. Class X-8 as an experimental class and class X-9 as a control class with totalling 32 students. The instrument for student learning outcomes is a multiple-choice test, and KPM was an essay test. The learning outcomes and KPM posttest in experimental class with PBL models were 77.97 and 62.78 while the control class with conventional learning was 70.3 and 41.8. Hypothesis testing shows the final learning outcomes and KPM of the two classes were different. The results concluded that there was an influence of PBL model on student learning outcomes and students’ KPM, there was an improvement of PBL model on student learning outcomes and students’ KPM, and an improvement in each indicator of KPM in the experimental class was bigger than conventional class.Keywords: problem-based learning, learning outcomes, problem-solving skills